(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2011)
The effective and universal algorithm of diffraction characteristics calculation of the field scattered by 2D rectangular element frequency-selective surface. Galerkin method was used to solve equations, received from boundary conditions. The system of linear algebraic equations of finite order was solved. For the field’s description of given 2D periodic structure in the terms of space harmonics Floquet theorem was used. Results obtained in the work match data from foreign sources. Computer program based on the algorithm might be used for reflection and transmission characteristics calculation of the structures with unit cell different sizes.